An Evolutionary Change in First Case on Time Starts Using Perioperative Process Improvement, Communication and Enhanced Data Integrity - Robert P. Foglia; MD; FACS; Juan E. Ruiz; MHA; Lorrie S. Burkhalter MPH (Global Journal of Perioperative Medicine - Peertechz Publications, 2017)
Background: First Case on Time Starts (FOTS) are an important Operating Room performance metric. The study aim is to show how implementation of process improvement (PI) solutions and an electronic health record (EHR) led to a progressive, significant, and sustainable improvement in FOTS. Methods: FOTS were tracked in the Main OR Suite (MOR) at Children's Medical Center Dallas, from January 2007 through March 2014. Approximately 17,000 scheduled first cases were evaluated. Significance was set at p<0.05. Results: FOTS were 12% in 2006. An OR Collaborative Redesign, implementation of a preoperative clinic and a change the preoperative phone call increased FOTS to 32% by early 2009. In 2009, an EHR was implemented. The EHR, its ability to identify specific accountability for delay (surgeon, anesthesiologist, and nurse, patient, other) and improved data integrity, increased FOTS to 60% by 2012. Using enhanced communication methods such as real time communication to staff, and data socialization, OTS further improved to 80% by 2014.